Numerical simulation of an explosion in a simple scale model of a nuclear reactor - Robbe, Marie-France; Lepareux, Michel; Treille, Eloi; Cariou, Yves (Computer Assisted Methods in Engineering and Science, 2002)
In the case of a Hypothetical Core Disruptive Accident (HCDA) in a Liquid Metal Fast Breeder Reactor, it is assumed that the core of the nuclear reactor has melted partially and that the chemical interaction between molten fuel and liquid sodium creates a high pressure gas bubble in the core. The violent expansion of this bubble loads and deforms the reactor vessel, thus endangering the safety of the nuclear plant. The experimental test MARA 8 simulates the explosive phenomenon in a mock-up enclosed in a flexible vessel with a flexible roof. This paper presents a numerical simulation of the test and a comparison of the computed results with the experimental results and previous numerical ones.